Implementasi Putusan Mahkamah Konstitusi Nomor 67/PUU-XI/2013 Terkait Kedudukan Upah Pekerja dalam Kepailitan (Implementation of Constitutional Court Decision Number 67/PUU-XI/2013 Related to the Position of Workers' Wages in Bankruptcy) - Luthvi Febryka Nola (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2019)
The position of creditors plays an important role in bankruptcy. The position would fortunate the creditors in receiving immediate payment, but unfortunately would also burden the creditors with unpaid debt settlement. Prior to the Constitutional Court Decision Number 67/PUU-XI/2013, the positions of creditors were separatist, preferred and concurrent creditors. Workers' wages are included in preferred creditors. However, the Constitutional Court Decision Number 67/PUU-XI/2013 has changed the position of creditors and put workers’ wages higher than other creditors. The decision also positioned other workers’ rights in a dominant compared to other preferred creditors. Therefore, this paper discusses Constitutional Court Decision Number 67/PUU-XI/2013 from the perspective of the strength of binding decisions and their implementation to relevant stakeholders. As for the results of the discussion, it can be seen that the Constitutional Court Decision has binding force once it was decided. However, because the Constitutional Court Decision Number 67/PUU-XI/2013 brings consequences for several laws, related laws need to be adjusted. At present, adjustments have not yet been made, and as a result, the implementation of the Decision is challenged with uncertainty, injustice, ineffectiveness, uselessness, and law smuggling. AbstrakKedudukan kreditor memegang peranan penting dalam kepailitan. Kedudukan akan membuat kreditor mendapatkan pembayaran terlebih dahulu namun juga dapat membuat kreditor tidak mendapatkan perlunasan hutang. Sebelum adanya Putusan Mahkamah Konstitusi (MK) Nomor 67/PUU-XI/2013, kedudukan kreditor adalah kreditor separatis, preferen dan konkuren. Upah pekerja termasuk dalam kreditor preferen. Putusan MK Nomor 67/PUU-XI/2013 telah mengubah posisi tersebut dan meletakkan posisi upah buruh di atas kreditor lainnya. Putusan ini juga memposisikan hak pekerja lain pada posisi utama dibandingkan kreditor preferen lainnya. Oleh karena itu tulisan ini membahas Putusan MK Nomor 67/PUU-XI/2013 dari perspektif kekuatan mengikat putusan dan implementasinya terhadap stakeholders terkait. Adapun dari hasil pembahasan dapat diketahui putusan MK memiliki kekuatan mengikat begitu diputuskan hanya saja karena Putusan MK Nomor 67/PUU-XI/2013 berpengaruh terhadap sejumlah undang-undang (UU) membuat UU terkait tersebut perlu disesuaikan. Saat ini penyesuaian belum dilakukan dan akibatnya dalam implementasi putusan terjadi ketidakpastian, ketidakadilan, ketidakefektifan, ketidakmanfaatan, dan penyelundupan hukum.